Composite nanofiltration membrane based on silicon dioxide nanoparticle modification as well as preparation and application of composite nanofiltration membrane
By introducing silica nanoparticles into graphene oxide films and using vacuum suction filtration and heat crosslinking treatment, the problem of unstable and poor permeability of graphene oxide films in aqueous solution is solved, and a composite nanofiltration membrane with high water flux and retention is achieved, which is suitable for treating wastewater containing high concentrations of inorganic salts and dyes.
Patent Information
- Application Number
- CN202510097417.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-03-28
AI Technical Summary
The existing graphene oxide films are unstable in aqueous solutions, have poor permeability, and it is difficult to achieve high water flux and retention rate at the same time.
By introducing silica nanoparticles into graphene oxide films and using vacuum suction filtration and heat crosslinking treatment, a composite nanofiltration membrane based on silica nanoparticles was prepared.
It improves the water flux and retention rate of the composite nanofiltration membrane, enhances the stability and durability of the membrane, and is suitable for treating wastewater containing high concentrations of inorganic salts and dyes.
Smart Images

Figure CN119701666A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of separation membrane materials, and more specifically to a composite nanofiltration membrane modified based on silicon dioxide nanoparticles and the preparation and application thereof. Background Art
[0002] As a new type of self-assembled membrane material, graphene oxide (GO) has attracted much attention for its unique honeycomb two-dimensional structure, large surface area, hydrophilicity, flexibility and chemical stability. The composite nanofiltration membrane based on graphene oxide thin film has a good removal effect on dye wastewater. However, the current graphene oxide film still has the following limitations: (1) Due to the electrostatic repulsion and hydration between the hydroxyl, carbonyl and epoxy groups on the graphene oxide nanosheets, the graphene oxide-based self-assembled membrane is extremely unstable in aqueous solution and is easy to swell, peel off and redisperse into the aqueous solution; (2) The interlayer spacing between adjacent graphene oxide nanosheets is narrow, resulting in poor membrane permeability. Therefore, it is necessary to improve the flux and permeability of graphene oxide films.
[0003] At present, there are a series of methods for modifying graphene oxide films, such as intercalation composite modification, functional group grafting, chemical modification, etc., mainly through the use of covalent bonds, π-π bond interactions or electrostatic interactions, various functional substances are introduced into the graphene oxide surface to enhance the interlayer steric effect, adjust the surface amphiphilicity, improve its dispersibility and compatibility with polymers, so that the graphene oxide film can achieve better separation effect in practical applications. Among them, intercalation composite modification can intercalate materials such as silicon dioxide nanoparticles, titanium dioxide nanoparticles, metal organic frameworks into graphene oxide, change the interlayer spacing, and obtain a composite nanofiltration membrane with better separation performance. However, due to the trade-off effect between water flux and retention rate, it is difficult to obtain a composite nanofiltration membrane with both good water flux and retention rate.
[0004] Therefore, there is an urgent need for a composite nanofiltration membrane with both good water flux and retention rate. Summary of the invention
[0005] 1. Technical problem to be solved by the invention
[0006] In view of the shortcomings of the poor performance of graphene oxide films in the prior art, a method for preparing a composite nanofiltration membrane based on modified silica nanoparticles having both good water flux and retention rate is provided; at the same time, a composite nanofiltration membrane based on modified silica nanoparticles and its application are also provided.
[0007] 2. Technical solution
[0008] In order to achieve the above object, the technical solution provided by the present invention is:
[0009] The present invention provides a method for preparing a composite nanofiltration membrane based on modification of silicon dioxide nanoparticles, comprising the following steps:
[0010] S1, providing a mixed solution containing graphene oxide and silicon dioxide nanoparticles;
[0011] S2, using a vacuum filtration method to form a graphene oxide functional layer on the base membrane with the mixed solution, and then performing a thermal cross-linking treatment to obtain a composite nanofiltration membrane modified by silica nanoparticles;
[0012] Wherein, in step S1, in the mixed solution, the concentration of graphene oxide is 0.01wt% to 0.05wt%, and the concentration of silicon dioxide nanoparticles is 0.01wt% to 0.05wt%;
[0013] In step S2, the amount of the mixed solution used is 0.50-1.50 mL / cm 2 .
[0014] It should be noted that the concentration of graphene oxide is controlled to be 0.01wt% to 0.05wt%, the concentration of silicon dioxide nanoparticles is controlled to be 0.01wt% to 0.05wt%; the usage amount of the mixed solution is 0.50 to 1.50mL / cm 2 , which is conducive to the preparation of composite nanofiltration membranes with better water flux and retention rate.
[0015] On the other hand, by adopting the vacuum filtration method and controlling the mass concentration of graphene oxide and silicon dioxide nanoparticles, the prepared graphene oxide functional layer is effectively and stably attached to the base membrane and is not easy to fall off in the solution; moreover, the graphene oxide functional layer is not easy to be damaged during the preparation process, thereby enhancing the durability of the composite nanofiltration membrane during use, such as during performance testing;
[0016] Thermal cross-linking treatment also promoted further cross-linking between the base membrane and the graphene oxide functional layer to improve the stability of the composite nanofiltration membrane.
[0017] It should also be noted that the amount of the mixed solution used refers to 0.50 to 1.50 mL of the mixed solution per square centimeter of effective filtration area.
[0018] Further, in step S1, in the mixed solution, the concentration of graphene oxide is 0.04wt% to 0.05wt%, and the concentration of silicon dioxide nanoparticles is 0.03wt% to 0.05wt%;
[0019] In step S2, the amount of the mixed solution used is 0.80-1.20 mL / cm 2 .
[0020] Preferably, in the mixed solution, the concentration of graphene oxide is 0.04wt%, and the concentration of silicon dioxide nanoparticles is 0.04wt%.
[0021] Furthermore, the base film includes one or more of a polyvinylidene fluoride (PVDF) film, a polyethersulfone film, and a cellulose film.
[0022] Preferably, the base film is a polyvinylidene fluoride film.
[0023] It should be noted that the polyvinylidene fluoride membrane has super strong tensile strength and strong acid resistance, which also improves the stability of the composite nanofiltration membrane. At the same time, when the polyvinylidene fluoride membrane is used as the base membrane, the composite nanofiltration membrane has good water flux and retention rate.
[0024] Furthermore, the pore size of the basement membrane is 0.45±0.05 μm.
[0025] Furthermore, in step S2, the conditions of the thermal cross-linking treatment include: a cross-linking temperature of 20 to 100° C. and a cross-linking time of 4 to 12 hours.
[0026] It should be noted that controlling the temperature and time of the thermal cross-linking treatment within the above range is conducive to obtaining a composite nanofiltration membrane with good retention rate and water flux.
[0027] Specifically, the cross-linking temperature may be 20 to 100°C, 40 to 100°C, 60 to 100°C or 80 to 100°C;
[0028] The cross-linking time may be 4 to 12 hours, 6 to 12 hours, 8 to 12 hours or 10 to 12 hours.
[0029] Furthermore, in step S1, the particle size of the silicon dioxide nanoparticles is 45 to 55 nm.
[0030] It should be noted that the use of silica nanoparticles within the above-mentioned particle size range is conducive to obtaining a composite nanofiltration membrane with good retention rate and water flux.
[0031] Furthermore, in step S1, the mixed solution can be obtained by the following method:
[0032] The graphene oxide dispersion is added into a solvent and mixed to obtain a uniform graphene oxide dilution; and silicon dioxide nanoparticles are added into the graphene oxide dilution to obtain a uniformly dispersed mixed solution.
[0033] It should be noted that adding silicon dioxide nanoparticles to the graphene oxide dilution solution and then mixing them can allow the silicon dioxide nanoparticles to be fully intercalated and cross-linked with the graphene oxide nanosheets.
[0034] Furthermore, mixing can be performed by ultrasound, centrifugation, magnetic stirring or mechanical stirring.
[0035] Preferably, when mixing by ultrasound, the ultrasound time is ≥ 0.5 h, preferably 0.5 to 1 h, and more preferably 0.5 h.
[0036] Furthermore, step S1 specifically includes: adding the graphene oxide dispersion into the solvent, ultrasonically mixing for ≥0.5h to obtain a graphene oxide dilution; and then adding silicon dioxide nanoparticles into the graphene oxide dilution, ultrasonically mixing for ≥0.5h to obtain a uniform mixed solution.
[0037] Furthermore, the solvent is one or more of deionized water and alcohol-based solvents.
[0038] Furthermore, the alcohol-based solvent may be one or more of methanol and ethanol.
[0039] Furthermore, in step S2, the negative pressure of the vacuum filtration is 0.8-1.0 MPa.
[0040] Furthermore, during vacuum filtration, the ambient temperature needs to be maintained at 20-30°C and the humidity at 60%-70%.
[0041] Preferably, during vacuum filtration, the ambient temperature should be maintained at 25° C. and the humidity should be maintained at 60%.
[0042] Furthermore, in step S2, the base film is subjected to a soaking treatment and a drying treatment in sequence before use.
[0043] Furthermore, the soaking treatment includes: soaking the base film in deionized water or toluene.
[0044] Furthermore, the soaking time is 5 to 10 minutes.
[0045] Furthermore, the drying process includes: drying until there is no obvious moisture on the surface of the base film.
[0046] Furthermore, the drying process includes: drying naturally in the air until there is no obvious moisture on the surface of the base film.
[0047] Furthermore, the drying process can be performed at room temperature.
[0048] The present invention also provides a composite nanofiltration membrane based on modification of silicon dioxide nanoparticles.
[0049] It comprises a base film and a graphene oxide functional layer, wherein the graphene oxide functional layer is loaded on the base film;
[0050] The graphene oxide functional layer comprises graphene oxide nanosheets of layered structure and silicon dioxide nanoparticles intercalated and cross-linked in the graphene oxide nanosheets;
[0051] The base film includes one or more of a polyvinylidene fluoride film, a polyethersulfone film, and a cellulose film.
[0052] It should be noted that in the graphene oxide functional layer, the silicon dioxide nanoparticles are intercalated and cross-linked between two adjacent graphene oxide nanosheets, and are also intercalated between adjacent graphene oxide nanosheets in the same layer. The silicon dioxide nanoparticles are intercalated and filled between two adjacent graphene oxide nanosheets. This filling effect can increase the distance between the sheets, expand the channels for water molecules to pass through, and increase the permeation flux to a certain extent. At the same time, SiO 2 Nanoparticles can react with oxygen-containing functional groups on the surface of GO to form silanols, for example, SiO 2 It reacts with -COOH on the GO surface to generate Si-OC bonds, and reacts with -O- and -OH to generate Si-O bonds. These newly generated chemical bonds with excellent heat resistance and stability form a cross-linked network, which can maintain the integrity of the nanofiltration membrane at high temperatures, lay the foundation for subsequent thermal cross-linking reactions, and improve the stability of the composite nanofiltration membrane; on the other hand, since silicon dioxide enters the transport channel of the graphene oxide nanosheets in the same layer, it regulates the pore structure, changes the pore size distribution of the membrane, and improves the separation performance of the membrane.
[0053] Furthermore, the base film is in surface contact with the graphene oxide functional layer.
[0054] Furthermore, the thickness of the graphene oxide functional layer is greater than 170 nm and less than 195 nm.
[0055] Furthermore, the thickness of the graphene oxide functional layer may be 180-195 nm, 180-190 nm or 185-190 nm.
[0056] Furthermore, the Zeta potential of the composite nanofiltration membrane is more negatively charged within the pH range of 3 to 9.
[0057] Furthermore, the Zeta potential of the composite nanofiltration membrane is negatively charged within a pH range of 4 to 9.
[0058] The present invention also provides an application of the composite nanofiltration membrane modified based on silica nanoparticles or the composite nanofiltration membrane modified based on silica nanoparticles prepared by the above preparation method in separating inorganic salts and dyes in water.
[0059] It should be noted that the composite nanofiltration membrane modified based on silica nanoparticles has good stability in the application of separating inorganic salts and dyes in water bodies, and also exhibits good permeability and retention performance under different operating pressures and feed concentrations. It can be used for the treatment of water bodies containing high concentrations of inorganic salts and dyes, such as dye wastewater.
[0060] Furthermore, the inorganic salt includes one or more of metal chlorides and metal sulfates.
[0061] Furthermore, the inorganic salt includes MgCl 2 , NaCl, MgSO 4 、Na 2 SO 4 One or more of the .
[0062] Furthermore, the dye includes one or more of disperse blue 15 (DB15), direct fast black 19 (DB19), vat brown 5 (VB5), and acid green 27 (AG27).
[0063] Furthermore, the dye is one or more of DB15, DB19, VB5, and AG27.
[0064] 3. Beneficial effects
[0065] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0066] (1) The preparation method of the composite nanofiltration membrane based on modified silicon dioxide nanoparticles provided by the present invention controls the concentration of graphene to be 0.01wt% to 0.05wt%, the concentration of silicon dioxide to be 0.01wt% to 0.05wt%; the amount of the mixed solution used is 0.80 to 1.20mL / cm 2 The overall performance of the prepared composite nanofiltration membrane is better.
[0067] (2) The method for preparing a composite nanofiltration membrane modified by silica nanoparticles provided by the present invention adopts a vacuum filtration method, so that the prepared layer containing graphene oxide is effectively and stably attached to the base membrane and is not easy to fall off in the solution; moreover, the graphene oxide functional layer is not easily damaged during the preparation process, thereby enhancing the durability of the composite nanofiltration membrane during use, such as during performance testing; on the other hand, the thermal cross-linking treatment also promotes further cross-linking between the base membrane and the graphene oxide functional layer to improve the stability of the composite nanofiltration membrane.
[0068] (3) In the graphene oxide functional layer of the composite nanofiltration membrane modified by silica nanoparticles provided by the present invention, the silica nanoparticles are intercalated and cross-linked between two adjacent layers of graphene oxide nanosheets, and are also intercalated between adjacent graphene oxide nanosheets in the same layer. The silica nanoparticles are intercalated and filled between two adjacent layers of oxide nanosheets. This filling effect can increase the distance between the sheets, expand the channels for water molecules to pass through, and increase the permeation flux to a certain extent. At the same time, SiO 2 Nanoparticles can react with oxygen-containing functional groups on the surface of GO to form silanols, for example, SiO 2 It reacts with -COOH on the GO surface to generate Si-OC bonds, and reacts with -O- and -OH to generate Si-O bonds. These newly generated chemical bonds with excellent heat resistance and stability form a cross-linked network, which can maintain the integrity of the nanofiltration membrane at high temperatures, lay the foundation for subsequent thermal cross-linking reactions, and improve the stability of the composite nanofiltration membrane; on the other hand, since silicon dioxide enters the transport channel of the graphene oxide nanosheets in the same layer, it regulates the pore structure, changes the pore size distribution of the membrane, and improves the separation performance of the membrane.
[0069] (4) The composite nanofiltration membrane modified based on silica nanoparticles provided by the present invention has good stability in the application of separating inorganic salts and dyes in water bodies, and also exhibits good permeability and retention performance under different operating pressures and feed concentrations. It can be used for the treatment of water bodies containing high concentrations of inorganic salts and dyes, such as dye wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 The effect of silicon dioxide concentration on the performance of the composite nanofiltration membrane in Example 1;
[0071] Figure 2 The effect of graphene oxide concentration on the performance of the composite nanofiltration membrane in Example 2;
[0072] Figure 3 The effect of cross-linking modification temperature on the performance of the composite nanofiltration membrane in Example 3;
[0073] Figure 4 The effect of cross-linking modification time on the performance of the composite nanofiltration membrane in Example 4;
[0074] Figure 5 The PVDF base membrane, PVDF-GO nanofiltration membrane, PVDF-GO-SiO 2 FTIR spectrum of composite nanofiltration membrane;
[0075] Figure 6 The PVDF base membrane (a), PVDF-GO nanofiltration membrane (b), PVDF-GO-SiO 2Surface (1) and cross-sectional (2, 3) morphologies of the composite nanofiltration membrane (c);
[0076] Figure 7 The PVDF base membrane, PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 Contact angle of composite nanofiltration membrane;
[0077] Figure 8 The PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 Zeta potential of composite nanofiltration membrane;
[0078] Fig. 9 The PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 Pure water permeation curve of composite nanofiltration membrane;
[0079] Fig.10 The PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 Molecular weight cut-off of composite nanofiltration membrane;
[0080] Fig.11 The PVDF-GO nanofiltration membrane of Example 7, PVDF-GO-SiO 2 Separation performance of composite nanofiltration membranes for different inorganic salts: (a) retention rate; (b) flux;
[0081] Fig.12 The PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 Separation performance of composite nanofiltration membrane for different dyes: (a) retention rate; (b) flux;
[0082] Fig.13 PVDF-GO-SiO in Example 9 2 Short-term stability test results of composite nanofiltration membrane;
[0083] Fig.14 PVDF-GO-SiO in Example 9 2 Long-term stability test results of composite nanofiltration membrane. DETAILED DESCRIPTION
[0084] The present disclosure may be more easily understood by reference to the following description in conjunction with examples, all of which constitute a part of the present disclosure. It should be understood that the present disclosure is not limited to the specific products, methods, conditions or parameters described and / or illustrated herein. Further, the terms used herein are only used for the purpose of describing specific embodiments by way of example and are not intended to be limiting unless otherwise indicated.
[0085] It should also be understood that, for the sake of clarity, certain features of the present disclosure may be described herein in the context of separate embodiments, but may also be provided in combination with each other in a single embodiment. That is, unless clearly incompatible or specifically not included, each separate embodiment is considered to be combinable with any other embodiment, and the combination is considered to represent another different embodiment. Conversely, for the sake of simplicity, the various features of the present disclosure described in the context of a single embodiment may also be provided individually or in any sub-combination. Finally, although a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure itself may also be considered to be an independent embodiment.
[0086] Unless otherwise indicated, it should be understood that each individual element in a list and each combination of individual elements in the list will be interpreted as a different embodiment. For example, a list of embodiments represented as "A, B, or C" should be interpreted to include embodiments "A", "B", "C", "A or B", "A or C", "B or C", or "A, B, or C".
[0087] In the present disclosure, the singular forms of the articles "a," "an," and "the" also include the corresponding plural references, and a reference to a specific value includes at least that specific value unless the context clearly indicates otherwise. Thus, for example, a reference to "a substance" is a reference to at least one of that substance and equivalents thereof.
[0088] When items are described by using the conjunction terms "... and / or...," etc., the description should be understood to include any one of the associated listed items and all combinations of one or more thereof.
[0089] In general, the use of the term "about" indicates an approximate value that can vary depending on the desired properties obtained by the disclosed subject matter, and will be interpreted in a context-dependent manner based on function. Therefore, one of ordinary skill in the art will be able to interpret a certain degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about". In other cases, a gradient in a range of values can be used to determine the range of differences allowed by the term "about". Further, all ranges in this disclosure are inclusive and combinable, and reference to a value in a range includes each value within that range.
[0090] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the terms used herein and / or include any and all combinations of one or more of the associated listed items.
[0091] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0092] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The essential characteristics and remarkable effects of the present invention can be reflected from the following examples, and the described embodiments are part of the embodiments of the present invention, rather than all the embodiments, and therefore, they do not limit the present invention in any way, and those skilled in the art make some non-essential improvements and adjustments based on the content of the present invention, which all belong to the protection scope of the present invention.
[0093] In the following embodiments
[0094] 1. The basic preparation steps of composite nanofiltration membrane modified by silica nanoparticles are as follows:
[0095] (1) First, prepare a graphene oxide dilution solution: add deionized water to a graphene oxide dispersion to prepare a graphene oxide dilution solution, and perform ultrasonic treatment for 0.5 h.
[0096] (2) Preparing a mixed solution: Adding silicon dioxide nanoparticles with a particle size of 50 nm into the graphene oxide diluted solution to prepare a mixed solution, and also performing ultrasonic treatment for 0.5 h.
[0097] (3) In an environment of 25°C and 60% relative humidity, the PVDF base film with a pore size of 0.45 μm was cut into pieces with an area of 25 cm 2 (Effective filtration area 12.56cm 2 ) was immersed in deionized water for 10 min, and then the excess water on the surface of the basement membrane was removed.
[0098] (4) After the surface of the base film in step (3) is dried until there is no obvious moisture, it is placed on a vacuum filtration device, and 15 mL of the mixed solution is filtered under a negative pressure of 0.8 MPa. The membrane obtained by filtration is then placed in an oven for thermal cross-linking treatment. The membrane after thermal cross-linking treatment is a composite nanofiltration membrane modified with silica nanoparticles (abbreviated as PVDF-GO-SiO 2 Composite nanofiltration membrane) needs to be soaked in deionized water before use.
[0099] 2. Characterization of composite nanofiltration membrane modified by silica nanoparticles is as follows:
[0100] (1) Fourier transform infrared spectroscopy (FTIR)
[0101] The present invention uses Nicolt iS5 Fourier infrared spectrometer to test the chemical structure of the composite nanofiltration membrane. Before the test, the composite nanofiltration membrane is placed in a 40°C vacuum oven to be thoroughly dried to avoid moisture interference. During the test, the stage where the composite nanofiltration membrane is to be placed is wiped with anhydrous ethanol and quickly blown dry with an ear bulb. The test surface of the membrane cut to an appropriate size is placed face down on the stage and pressed tightly before starting the test. The test wave number range is 400-4000cm -1 The spectrum can be used to qualitatively analyze the functional groups contained in the composite nanofiltration membrane.
[0102] (2) Scanning electron microscopy (SEM)
[0103] The Quanta FEG 250 thermal field emission scanning electron microscope was used to observe the sample film morphology and cross-sectional microstructure. Before the test, a 24-hour drying operation was required. During the test, the sample film surface and the cross-section after liquid nitrogen quenching (to prevent damage to the membrane pores) were sprayed with gold to enhance its conductivity, and then observed in the observation room to obtain the surface morphology and cross-sectional structure at different magnifications.
[0104] (3) Contact angle (WCA)
[0105] The present invention uses a DSA30 contact angle meter to test the wettability of the composite nanofiltration membrane surface by water in the air. Before the test, the membrane sample must be fully dried. During the test, the membrane sample is cut into a suitable size and placed on the test bench. The focal length is adjusted, and a small drop of ultrapure water is transferred to the membrane surface. After staying for 10 seconds, the shape of the drop is captured with a high-speed camera, and the static contact angle of the drop is measured. Each group of results is tested 3 times and the average value is taken.
[0106] (4) Zeta potential
[0107] The present invention uses a Zeta potential analyzer of model SurPASSTM3 for testing. Before the test, the membrane sample to be tested is cut into a suitable size and the membrane surface is kept wet. The pH range of the test is 3-9, so as to obtain the charge of the membrane under different pH conditions.
[0108] 3. PVDF-GO-SiO2 modified by silica nanoparticles 2 Composite nanofiltration membrane for MgCl 2 The calculation of solution retention rate and permeation flux is as follows:
[0109] In order to ensure the accuracy of the experimental data, the sample membrane was pre-pressed for 30 min at 0.8 MPa before the experiment to obtain a stable flux, and then the effective membrane area of 12.56 cm was tested at an inlet pressure of 0.8 MPa. 2The cross-flow filtration experiment was carried out on the nanofiltration membrane performance evaluation device to record the performance of the composite nanofiltration membrane at 0.5 g / L MgCl under different experimental conditions. 2 The experiment was carried out at room temperature, and permeate samples for flux measurement and retention evaluation were collected every half an hour. Each result was repeated at least three times to reduce experimental errors. The permeate flux was obtained by measuring the permeate volume, and the retention rate was obtained by measuring the conductivity of the permeate and the feed solution, which were calculated according to formulas (1) and (2), respectively:
[0110] J=V / (A×ΔT) (1)
[0111] Where: J—permeation flux, L·m -2 ·h -1 MPa -1 ;
[0112] V—volume of osmotic solution, L;
[0113] A—Effective filtration area of the membrane, m 2 ;
[0114] ΔT—Time required for filtration, h.
[0115] R=(1-C p / C f )×100% (2)
[0116] In the formula, C p -Permeate concentration, g / L;
[0117] C f -Feed liquid concentration, g / L;
[0118] R-retention rate, %.
[0119] 4. PVDF-GO-SiO2 modified by silica nanoparticles 2 The pure water permeability coefficient of the composite nanofiltration membrane is determined as follows:
[0120] The present invention adopts cross-flow filtration experiment to carry out PVDF-GO-SiO 2 The pure water permeability coefficient of the composite nanofiltration membrane was determined by first pre-pressing the prepared composite nanofiltration membrane at 0.8 MPa for 30 min to obtain a stable membrane flux. Then, the membrane was placed under different operating pressures (0.3, 0.5, 0.7, 0.9, and 1.1 MPa) to measure the pure water flux. According to the Spiegler-Kedem theoretical model (Formula 3), the pressure-flux curve was fitted to obtain the PVDF-GO-SiO 2 Pure water permeability coefficient of composite nanofiltration membrane.
[0121] J v =Lp (ΔP-σΔπ) (3)
[0122] In the formula, J v -Solvent penetration rate, L·m -2 ·h -1 ;
[0123] L p -Permeability coefficient of the solvent, L·m -2 ·h -1 MPa -1 ;
[0124] ΔP-pressure difference between membrane surfaces, MPa;
[0125] σ is the reflection coefficient of the film;
[0126] Δπ-osmotic pressure, MPa.
[0127] 5. PVDF-GO-SiO2 modified by silica nanoparticles 2 Molecular weight cut-off and Stokes radius of composite nanofiltration membrane
[0128] The molecular weight cut-off (MWCO) refers to the molecular weight corresponding to a substance retention rate of 90%, which can be used to indirectly calculate the pore size of the nanofiltration membrane. -1 Neutral polyethylene glycol (PEG) with different molecular weights (400, 600, 800, 1000, 1500) was used as the interception object. The PVDF-GO-SiO 2 The composite nanofiltration membrane was used for cross-flow filtration experiments. The retention rate was calculated by testing the concentration of the raw liquid and the permeate with a total organic carbon (TOC) analyzer. The retention curve was drawn and the PVDF-GO-SiO 2 Stokes radius of composite nanofiltration membrane (r s ), the molecular weight and Stokes radius of PEG are shown in Table 1.
[0129] r s =16.73×10 -12 ×M 0.557 (4)
[0130] In the formula, r s - Stocks radius of the membrane, m;
[0131] M - molecular weight cut-off of the membrane.
[0132] Table 1 PEG molecular weight and Stokes radius
[0133]
[0134] Example 1
[0135] The preparation of the composite nanofiltration membrane modified by silica nanoparticles in this embodiment is basically the same as the above-mentioned "1. Basic preparation steps of the composite nanofiltration membrane modified by silica nanoparticles".
[0136] On this basis, a mixed solution with different silicon dioxide nanoparticle concentrations in the range of 0.01wt% to 0.05wt% is provided.
[0137] Other film-forming conditions are as follows: the graphene oxide concentration in the mixed solution is 0.04 wt %, the cross-linking temperature of the thermal cross-linking treatment is 80° C., and the cross-linking time is 10 h.
[0138] Finally, a composite nanofiltration membrane modified based on silica nanoparticles was prepared.
[0139] According to the above “3. PVDF-GO-SiO2 modified by silica nanoparticles 2 Composite nanofiltration membrane for MgCl 2 The changes in the flux and retention rate of the composite nanofiltration membrane modified by silica nanoparticles prepared in this example are shown in the "Calculation of solution retention rate and permeation flux" section. The final trend is as follows Figure 1 .
[0140] Depend on Figure 1 It can be seen that with the SiO 2 With the increase of concentration, the interception rate has been increasing, and the increase is getting larger and larger. 2 When the concentration is 0.05wt%, the rejection rate is 83.2%. 2 As the concentration increases, the flux of the membrane increases first and then decreases. 2 When the addition amount was 0.04wt%, the maximum flux of the membrane was 12.33L·m -2 ·h -1 The possible reasons for this phenomenon are: (1) SiO 2 Nanoparticles enter the pore structure of graphene oxide, regulating the pore structure of the membrane and improving the separation performance of the membrane. 2 The increase in particle mass makes the pores of the nanofiltration membrane smaller and smaller, so the retention rate of the composite nanofiltration membrane has a good trend. (2) SiO 2 Nanoparticles can fill the gaps between graphene oxide sheets, expand the channels through which water molecules can pass, and increase the permeation flux to a certain extent. 2 The particles gradually clog the membrane pores, so the permeation flux gradually decreases. (3) A small amount of SiO 2Nanoparticles can react with oxygen-containing functional groups (such as -COOH, -O-, etc.) on the surface of GO through surface modification reactions to form a cross-linked network. This reaction can form new -Si-OC- bonds on the surface of GO sheets, which have excellent heat resistance and stability, can maintain their structural integrity at high temperatures, and lay the foundation for subsequent thermal cross-linking reactions.
[0141] Example 2
[0142] The preparation of the composite nanofiltration membrane modified by silica nanoparticles in this embodiment is basically the same as the above-mentioned "1. Basic preparation steps of the composite nanofiltration membrane modified by silica nanoparticles".
[0143] On this basis, a mixed solution with different graphene oxide concentrations in the range of 0.01wt% to 0.05wt% is provided.
[0144] Other film-making conditions are as follows: the content of silica nanoparticles in the mixed solution is 0.04 wt %, the cross-linking temperature of the thermal cross-linking treatment is 80° C., and the cross-linking time is 10 h.
[0145] Finally, a composite nanofiltration membrane modified based on silica nanoparticles was prepared.
[0146] According to the above “3. PVDF-GO-SiO2 modified by silica nanoparticles 2 Composite nanofiltration membrane for MgCl 2 The changes in the flux and retention rate of the composite nanofiltration membrane modified by silica nanoparticles prepared in this example are shown in the "Calculation of solution retention rate and permeation flux" section. The final trend is as follows Figure 2 .
[0147] Depend on Figure 2 It can be seen that with the increase of GO concentration, the permeation flux of the membrane shows a trend of first increasing and then decreasing, while the rejection rate has been increasing. When the GO concentration increases from 0.01wt% to 0.03wt%, the flux of the composite nanofiltration membrane increases from 10.03L·m -2 ·h -1 becomes 12.90L·m -2 ·h -1 The increase in flux is mainly due to the fact that the cross-linking between the excessive graphene oxide sheets may form some relatively open channels, which helps to increase the water flux. This is because the cross-linking may change the pore structure of the membrane to a certain extent, making it more conducive to the rapid passage of water molecules. However, as the GO concentration increases further, the membrane flux increases from 12.90 L·m -2 ·h -1 Reduced to 11.94 L·m -2 ·h -1, because excessive cross-linking may cause the membrane pores to be closed or blocked, resulting in a decrease in water flux.
[0148] Example 3
[0149] The preparation of the composite nanofiltration membrane modified by silica nanoparticles in this embodiment is basically the same as the above-mentioned "1. Basic preparation steps of the composite nanofiltration membrane modified by silica nanoparticles".
[0150] On this basis, it is set up that: heat cross-linking treatment is carried out at different temperatures within the range of 20 to 100°C.
[0151] Other film-forming conditions are as follows: the content of silicon dioxide nanoparticles in the mixed solution is 0.04 wt %, the concentration of graphene oxide is 0.04 wt %, and the cross-linking time of the thermal cross-linking treatment is 10 h.
[0152] Finally, a composite nanofiltration membrane modified based on silica nanoparticles was prepared.
[0153] According to the above “3. PVDF-GO-SiO2 modified by silica nanoparticles 2 Composite nanofiltration membrane for MgCl 2 The changes in the flux and retention rate of the composite nanofiltration membrane modified by silica nanoparticles prepared in this example are shown in the "Calculation of solution retention rate and permeation flux" section. The final trend is as follows Figure 3 .
[0154] Depend on Figure 3 It can be seen that with the increase of thermal cross-linking temperature, the flux and retention rate of the composite nanofiltration membrane showed a trend of first increasing and then decreasing. At 80 °C, the maximum flux reached 12.33 L·m -2 ·h -1 , the maximum interception rate is 82.1%. This is mainly because as the thermal cross-linking temperature continues to increase, the SiO 2 The surface modification reaction between nanoparticles and GO consumes oxygen-containing functional groups on the membrane surface, increases the amount of -Si-OC- in the membrane, changes the chemical properties of the membrane surface, and improves the membrane's permeability. At the same time, the thermal cross-linking process also promotes the change of the membrane's pore structure, making the membrane pores more uniform and improving the membrane's retention. However, too high a thermal cross-linking temperature may cause the pores to be blocked or closed, reducing the effective pores of the membrane; at the same time, high temperatures may cause the membrane pores to become smaller, making it easier for small molecules to pass through the membrane pores, thereby reducing the separation ability and permeability of the membrane.
[0155] Example 4
[0156] The preparation of the composite nanofiltration membrane modified by silica nanoparticles in this embodiment is basically the same as the above-mentioned "1. Basic preparation steps of the composite nanofiltration membrane modified by silica nanoparticles".
[0157] On this basis, it is set up that the heat cross-linking treatment is carried out at different times within the range of 4 to 12 hours.
[0158] Other film-forming conditions are as follows: the content of silicon dioxide nanoparticles in the mixed solution is 0.04 wt %, the concentration of graphene oxide is 0.04 wt %, and the cross-linking temperature of the thermal cross-linking treatment is 80° C.
[0159] Finally, a composite nanofiltration membrane based on modified silica nanoparticles was prepared. 2 Composite nanofiltration membrane for MgCl 2 The changes in the flux and retention rate of the composite nanofiltration membrane modified by silica nanoparticles prepared in this example are shown in the "Calculation of solution retention rate and permeation flux" section. The final trend is as follows Figure 4 shown.
[0160] from Figure 4 It can be seen that with the increase of thermal cross-linking time, the water flux of the composite nanofiltration membrane showed a trend of rising and then falling, and the retention rate of the composite membrane continued to increase. The permeation flux reached the maximum at 10 h, which was 12.33 L·m -2 ·h -1 When the cross-linking time increased from 10 h to 12 h, the permeation flux of the membrane decreased to 8.76 L·m -2 ·h -1 , the retention rate increased from 82.1% to 84.2%. The reasons for this phenomenon may be: (1) Shorter thermal cross-linking time may lead to lower cross-linking density and fewer chemical bonds inside the membrane, which leads to the membrane structure being not tight enough and the surface chemical flux properties being not stable enough. (2) Shorter cross-linking time may cause the pore structure of the membrane to retain more of the original structure, the pore size and distribution may be more uniform, the membrane pores are larger, and the retention rate of smaller particles or molecules may be lower. Therefore, increasing the thermal cross-linking time can fully promote the SiO 2 The oxygen-containing functional groups of GO participate in the cross-linking reaction. After the reaction, the pore structure of the membrane may become more uniform, making it more conducive to the rapid passage of water molecules and increasing the permeation flux. At the same time, the cross-linking reaction leads to the improvement of the anti-fouling performance of the membrane surface, thereby increasing the retention rate of particles or molecules of certain sizes.
[0161] Comparative Example 1
[0162] The preparation of the PVDF-GO nanofiltration membrane in this comparative example is basically the same as the above-mentioned "1. Basic preparation steps of composite nanofiltration membrane modified by silica nanoparticles".
[0163] The only difference is: no silicon dioxide nanoparticles are added.
[0164] Other membrane preparation conditions are: the graphene oxide concentration in the mixed solution is 0.04wt%, the cross-linking temperature of the thermal cross-linking treatment is 80°C, and finally a PVDF-GO nanofiltration membrane is prepared.
[0165] Example 5
[0166] The PVDF-GO-SiO prepared in Example 4 was prepared according to the following conditions: the silica nanoparticles in the mixed solution were 0.04 wt%, the graphene oxide concentration was 0.04 wt%, the thermal crosslinking temperature was 80 °C, and the thermal crosslinking time was 10 h. 2 The composite nanofiltration membrane was compared with the PVDF base membrane and the PVDF-GO nanofiltration membrane prepared in Comparative Example 1, and the microscopic morphology and surface properties were characterized. The results are as follows:
[0167] Figure 5 PVDF-based membrane, PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 FTIR spectrum of the composite nanofiltration membrane. It can be seen from the figure that compared with the PVDF base membrane, the spectrum curve of the prepared PVDF-GO nanofiltration membrane contains a large number of characteristic peaks. -1 and 1620cm -1 There is a large and strong absorption peak at 1725cm, which indicates that graphite contains a large number of water molecules. -1 The characteristic absorption peak at 1620 cm is due to the stretching vibration of the C=0 bond of the -COOH group. -1 The characteristic peak at 1424cm is caused by the C=C vibration in the carbon lattice. -1 and 1351cm -1 The peaks are C-OH and CO stretching vibration peaks respectively. The symmetrical stretching vibration of COC leads to 1047cm -1 The above shows that GO contains a large number of oxygen-containing functional groups such as carbonyl, carboxyl, and epoxy groups. This structure makes GO easily dispersed in water media. Compared with PVDF-based membranes, the prepared PVDF-GO-SiO 2 Composite nanofiltration membrane at 1040cm -1 、791cm -1 、1196cm -1 New resonance absorption peaks appeared, including at 1040cm -1 and 791cm -1The characteristic peak at 1196 cm -1 The characteristic absorption peak is due to the asymmetric vibration of Si-OC bond, which indicates that SiO 2 The nanoparticles reacted with the -COOH groups on the GO surface to form a cross-linked network. These observations confirmed the synthesis of silica on graphene oxide nanosheets via hydrolysis.
[0168] Figure 6 PVDF membrane (a), PVDF-GO nanofiltration membrane (b), PVDF-GO-SiO 2 (c) The surface (1) and cross-sectional morphology (2, 3) of the membrane. As can be seen from the figure, from Figure (a1), the surface of the PVDF base membrane is relatively smooth, with traces of folding caused by sporadic experiments. From (a2) and (a3), it can be seen that it presents a uniform asymmetric structure consisting of a typical finger-like porous support layer and a top selection layer of a microfiltration membrane. The thickness of the selection layer of the PVDF base membrane is about 235nm. From (b1), it can be seen that many obvious raised irregular nodes appear on the surface of the PVDF-GO nanofiltration membrane prepared by introducing GO molecules into the PVDF base membrane. This is mainly due to the uneven distribution and self-assembly behavior of GO molecules on the surface of the PVDF base membrane. GO molecules have a rigid and two-dimensional structure, which is easy to stack and fold on the surface of the base membrane, resulting in raised nodes on the surface. It can be seen from (b2) and (b3) that because GO molecules have a two-dimensional sheet structure, when they are uniformly dispersed in the PVDF-based membrane, the GO sheets form staggered stacks in the membrane, making the graphene oxide layer more dense and compact, thereby compressing the thickness of the graphene oxide layer to about 170 nm;
[0169] As can be seen from (c1), the introduction of SiO into the PVDF-GO nanofiltration membrane 2 After the nanoparticles were added, very fine nodular structures with increasing numbers were observed on the film surface, which indicated that SiO 2 The nanoparticles are uniformly intercalated between the membrane layers, increasing the roughness of the membrane surface and resulting in more nodular structures. 2 Compared with the previous two membranes, the composite nanofiltration membrane has many flaky wrinkles on the membrane surface, which is mainly due to the SiO 2 The uniform dispersion of nanoparticles on the membrane surface increases the surface roughness and irregularity, forming more flake-like wrinkled structures. 2 The finger-like porous support layer of the composite nanofiltration membrane becomes shorter and smaller, which is mainly due to the SiO 2The embedding of nanoparticles changes the pore size and distribution of the support layer, the pore size becomes smaller and the number of pores decreases, causing the support layer to become shorter. In addition, there are obvious light and dark stripes in (c2). The darker area may correspond to the silica nanoparticles (yellow mark in (c2)), and the brighter area is the graphene oxide layer (red mark in (c2)). Because silica has a relatively strong scattering ability for electrons, while graphene oxide is weaker, this is the effect of alternating stacking of graphene oxide sheets and silica nanoparticles. At the same time, silica nanoparticles may be inserted between the graphene oxide sheets. In (c3), it can be found that the graphene oxide sheets have local expansion or increased spacing (orange mark in (c3)). When the structure after intercalation is observed under an electron microscope, the flatness of the graphene oxide sheets may be affected, and a certain degree of bending or wrinkling may occur. More importantly, the introduction of SiO on the PVDF-GO nanofiltration membrane 2 After the nanoparticles were deposited, the thickness of the graphene oxide functional layer was 185 nm, which was mainly due to the SiO 2 Nanoparticles are intercalated between GO sheets to expand the interlayer spacing, making the membrane structure denser and stronger. However, compared with PVDF-based membranes, due to the stacking structure of GO molecules, the thickness of the selective layer of PVDF-GO nanofiltration membrane composite nanofiltration membrane is still lower than that of PVDF-based membranes.
[0170] Figure 7 PVDF-based membrane, PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 The WCA result of the composite nanofiltration membrane shows that the contact angle of the PVDF-based membrane is 5.28°. After the PVDF-GO nanofiltration membrane is formed by pressure filtration on its surface, the hydrophilicity of the membrane is greatly improved due to the abundant oxygen-containing groups on the surface of GO, which is 29.21° as shown in the figure. 2 The SiO2 reacts with -COOH on the GO surface to generate Si-OC with good hydrophilicity, which significantly increases the oxygen-containing functional groups on the GO surface. The presence of these groups makes the GO surface more likely to interact with water molecules and improve its hydrophilicity. 2 It contains abundant Si-OH, which can form hydrogen bonds with water molecules, thus showing hydrophilicity and making the nanofiltration membrane more likely to adsorb water molecules. 2 The contact angle is 42.31°.
[0171] Figure 8 PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 Zeta potential results of composite nanofiltration membranes. It can be seen from the figure that PVDF-GO nanofiltration membrane and PVDF-GO-SiO2 The equipotential point of the composite nanofiltration membrane is about 3.75. As the pH increases from 3 to 9, the surface potential of both membranes changes from positive to negative. This is because the GO surface contains abundant oxygen-containing functional groups (such as carboxyl, epoxy and hydroxyl groups), which will ionize under different pH conditions. Under low pH conditions (such as pH < 3.75), these oxygen-containing functional groups mainly exist in a non-ionized form, and the membrane surface has a net positive charge; as the pH increases, these functional groups gradually ionize and release negative ions, which increases the negative charge on the membrane surface. For example, -COOH ionizes to -COO- at pH > 3.75, and -O- and hydroxyl-OH also gradually ionize to -O- and -OH- at pH > 3.75. These ionization processes lead to an increase in the negative charge on the membrane surface, which causes the surface potential to change from positive to negative. In addition, it can be seen that at the same pH value (pH > 3.75), PVDF-GO-SiO 2 The electronegativity of the composite nanofiltration membrane is higher than that of the PVDF-GO nanofiltration membrane, which is mainly due to the SiO 2 Nanoparticles form more silicon-oxygen bonds and silicon-ester bonds on the membrane surface, increasing the density of negative charges. 2 Composite nanofiltration membrane has a good prospect for treating charged ions in dye wastewater.
[0172] Example 6
[0173] The PVDF-GO-SiO prepared in Example 4 was prepared according to the following conditions: the silica nanoparticles in the mixed solution were 0.04 wt%, the graphene oxide concentration was 0.04 wt%, the thermal crosslinking temperature was 80 °C, and the thermal crosslinking time was 10 h. 2 The separation performance of the composite nanofiltration membrane was determined, and the final trend was as follows Fig. 9 and Fig.10 shown.
[0174] (1) Pure water permeability coefficient
[0175] The PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 The pure water permeability coefficient curve and equation of the composite nanofiltration membrane are as follows: Fig. 9 As shown in Table 2. The pure water permeability coefficient of PVDF-GO nanofiltration membrane is calculated by formula (3) to be 28.54 L·m -2 ·h -1 MPa -1 When hydrophilic SiO 2 After the nanoparticles are added, the hydrophilicity of the membrane surface is improved, making PVDF-GO-SiO 2 The pure water permeability coefficient of the composite nanofiltration membrane was increased to 91.32 L·m -2 ·h -1MPa -1 .
[0176] Table 2 Regression equation of pure water permeability curve
[0177]
[0178] (2) Molecular weight cut-off and Stocks radius
[0179] The present invention uses 1g·L -1 Neutral polyethylene glycols of different molecular weights (400, 600, 800, 1000, 1500) were tested for retention. The results are as follows: Fig.10 As shown in the figure, as the molecular weight of PEG increases, the 2 The retention rate of the composite nanofiltration membrane has been improved. This is because the larger the molecular weight of PEG, the larger its corresponding Stokes radius, and the more difficult it is to pass through the membrane pores. As shown in the figure, the MWCO of the PVDF-GO nanofiltration membrane is 560Da, and the PVDF-GO-SiO 2 The MWCO of the composite nanofiltration membrane is 930Da. According to formula (4), the Stokes radius of the PVDF-GO nanofiltration membrane is 0.554nm, and the PVDF-GO-SiO 2 The Stokes radius of the composite nanofiltration membrane is 0.783nm.
[0180] Example 7
[0181] The PVDF-GO-SiO prepared in Example 4 was prepared according to the following conditions: the silica nanoparticles in the mixed solution were 0.04 wt%, the graphene oxide concentration was 0.04 wt%, the thermal crosslinking temperature was 80 °C, and the thermal crosslinking time was 10 h. 2 The separation performance of inorganic salts was determined by composite nanofiltration membrane, and the final trend was as follows Fig.11 shown.
[0182] The present invention uses cross-flow filtration to filter four 0.5g / L inorganic salts (Na 2 SO 4 MgSO 4 MgCl 2 The water permeation flux and retention rate of the composite nanofiltration membrane for inorganic salts were calculated according to formula (1) and formula (2) to evaluate the separation performance of the composite nanofiltration membrane for inorganic salts. The physicochemical properties of some ions are shown in Table 3. Before the experiment, the composite nanofiltration membrane was pre-pressed at 0.8 MPa for 30 min to obtain a stable flux. Each group of experiments was measured three times in parallel to obtain the average value.
[0183] Table 3 Inorganic salt ion parameters
[0184]
[0185] Fig.11 The PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 The permeation flux and retention rate of the composite nanofiltration membrane for four inorganic salts. As can be seen from Figure (a), the addition of SiO 2 After that, the permeation flux of the nanofiltration membrane increased, which was mainly attributed to: First, SiO 2 The nanoparticles react with the -COOH on the GO surface to generate new chemical bonds, which increase the hydrophilic functional groups on the membrane surface and the SiO 2 It is also hydrophilic. Secondly, SiO 2 Nanoparticles expand the interlayer spacing and change the membrane pore structure by filling between GO sheets, making the originally tightly arranged sheets looser and increasing the effective size of the membrane pores, effectively reducing the resistance of water molecules passing through the membrane, thereby increasing the permeation flux; third, GO and SiO 2 The formation of the cross-linked network improves the structural stability of the membrane, allowing the membrane to maintain a high water flux under high operating pressure. 2 The interception order of the composite nanofiltration membrane for the four inorganic salts is: MgCl 2 (87.21%)>Mg 2 SO 4 (83.14%)>Na 2 SO 4 (68.32%)>NaCl(67.39%), which is consistent with the typical separation characteristics of negatively charged nanofiltration membranes. The retention of charged solutes by nanofiltration membranes mainly depends on the Donan effect, steric hindrance effect and electrostatic repulsion. From the Zeta potential data, it can be seen that PVDF-GO-SiO 2 The composite nanofiltration membrane is a negatively charged membrane. According to the Donnan effect, its repulsion to divalent anions is stronger than that to monovalent anions, that is, PVDF-GO-SiO 2 The nanofiltration membrane has the lowest retention rate for NaCl. 2+ In the case of Cl - The hydration radius (0.242nm) is smaller than SO 4 2- (0.230nm), due to the screening effect, Cl - Than SO 4 2- It is easier to pass through the membrane pores, so MgCl 2 The retention rate is greater than that of Mg 2 SO 4 ; When the divalent anion is SO4 2- In the case of Mg 2+ and Na + The hydration radius of Na + The amount of positive charge is less than Mg 2+ , composite nanofiltration membrane for Na + The attraction is less than that of Mg 2+ , resulting in PVDF-GO-SiO 2 Composite nanofiltration membrane for Na 2 SO 4 The retention rate is less than that of Mg 2 SO 4 Compared with the retention order of inorganic salts by PVDF-GO nanofiltration membrane, only NaCl and Na 2 SO 4 The position of is reversed. The main reason for this change is: adding SiO 2 After the addition of 2% MgCl, the interlayer spacing of the membrane increases, the pore structure becomes more uniform, and the hydrophilicity of the membrane surface increases, which significantly reduces the retention rate of the membrane for small-sized ions NaCl and significantly increases the retention rate of medium-sized ions NaCl. 2 SO 4 The interception rate has been improved.
[0186] Example 8
[0187] The PVDF-GO-SiO prepared in Example 4 was prepared according to the following conditions: the silica nanoparticles in the mixed solution were 0.04 wt%, the graphene oxide concentration was 0.04 wt%, the thermal crosslinking temperature was 80 °C, and the thermal crosslinking time was 10 h. 2 The separation performance of the composite nanofiltration membrane was determined, and the final trend was as follows Fig.12 shown.
[0188] The present invention uses cross-flow filtration to perform an interception test on 0.5 g / L of four dyes (disperse blue 15, vat brown 5, acid green 27, and direct sun-fast black 19) at 0.8 MPa. The properties of the four dyes are shown in Table 4, and the regression equations of the standard curves of the four dyes are shown in Table 5. Before the experiment, it is necessary to first determine the concentration of the dye and the regression equation of the absorbance standard curve. The specific operation is: first use an ultraviolet spectrophotometer to scan the maximum absorption peak of the dye, and then use the external standard method to make a standard curve at the wavelength of the maximum absorption peak. Substitute the absorbance of the stock solution and the permeate into the regression equation to obtain the concentration, and then calculate the interception rate according to Formula 2 to obtain PVDF-GO-SiO 2 Separation performance of composite nanofiltration membrane for four dyes.
[0189] Table 4 Dye related parameters
[0190]
[0191]
[0192] Table 5 Regression equation of dye concentration and absorbance
[0193]
[0194] Where x is the dye concentration (mg / L) and y is the absorbance.
[0195] Fig.12 The PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2 The permeation flux and retention rate of the composite nanofiltration membrane for the four dyes can be seen from Figure (a). 2 After that, the permeation flux of the nanofiltration membrane increased to varying degrees. The reason for this phenomenon is: Figure 8 It can be seen that PVDF-GO-SiO 2 The electronegativity of the composite nanofiltration membrane is higher than that of the PVDF-GO nanofiltration membrane, which strengthens the electrostatic effect on the charged dye, resulting in an increase in the permeation flux. 2 The permeation flux of the composite nanofiltration membrane for dyes showed different trends. The flux of the composite nanofiltration membrane for DB15 increased from 6.41 L·m -2 ·h -1 Increased to 12.89 L·m -2 ·h -1 , the flux to VB5 increased from 5.85 L·m -2 ·h -1 Increased to 11.82 L·m -2 ·h -1 , almost doubled, but the flux of composite nanofiltration membrane for AG27 and DB19 only increased slightly. The reason for this phenomenon is that the composite nanofiltration membrane is 2 After modification, the hydrophilicity increases and the effective size of the membrane pore size increases. For the positively charged DB15 and the uncharged VB5, the negative charge on the membrane surface leads to a stronger electrostatic repulsion effect, which significantly increases the flux of these two dyes. In contrast, AG27 and DB19 are negatively charged themselves, and produce a strong electrostatic repulsion effect with the negative charge on the membrane surface. However, due to the small size of these two dyes, the electrostatic repulsion effect has a relatively small effect on their flux, resulting in a small increase in flux. Therefore, the composite nanofiltration membrane significantly improves the flux of DB15 and VB5, but has a smaller increase in the flux of AG27 and DB19. As can be seen from Figure (b), the addition of SiO 2 After that, the dye retention rate of the nanofiltration membrane was slightly improved, and the PVDF-GO nanofiltration membrane and PVDF-GO-SiO 2The dye interception order of the composite nanofiltration membrane is basically the same. 2 The interception order of the composite nanofiltration membrane for dyes is: VB5 (96.52%) > DB15 (96.43%) > AG27 (95.87%) > DB19 (89.21%). This interception order is mainly related to the size and shape of the dye molecules. Specifically, the molecular size of VB5 and DB15 is larger and the shape is more complex, which makes it more difficult to pass through the membrane pores, so the interception rate is higher; while the molecular size of AG27 and DB19 is smaller or the shape is more regular, which makes it relatively easy to pass through the membrane pores, so the interception rate is lower. PVDF-GO-SiO 2 The surface negative charge of the composite nanofiltration membrane is enhanced, and DB15 (positively charged) will be attracted by the negative charge on the membrane surface, resulting in more adsorption and retention; while VB5 (uncharged) is more easily captured by the negative charge on the membrane surface through the enhanced van der Waals force. 2 The retention rate of DB15 and VB5 of the composite nanofiltration membrane increased. At the same time, the negative charge on the membrane surface produced a strong electrostatic repulsion with the negatively charged AG27 and DB19. This repulsion made it more difficult for the negatively charged dye molecules to pass through the membrane pores, thereby increasing the retention rate.
[0196] Example 9
[0197] The PVDF-GO-SiO prepared in Example 4 was prepared according to the following conditions: the silica nanoparticles in the mixed solution were 0.04 wt%, the graphene oxide concentration was 0.04 wt%, the thermal crosslinking temperature was 80 °C, and the thermal crosslinking time was 10 h. 2 The short-term and long-term stability of the composite nanofiltration membrane were determined, and the final trends were as follows: Fig.13 and Fig.14 shown.
[0198] The present invention is directed to PVDF-GO-SiO 2 The composite nanofiltration membrane design experiment explored its short-term stability (24h) and long-term stability (70h) under different conditions. In the short-term stability test, 0.5g / L DB15 dye solution was used as the feed liquid, and PVDF-GO-SiO 2 The composite nanofiltration membrane was continuously filtered for 24 hours, and the flux and retention rate of the nanofiltration membrane were recorded every hour. The test results are as follows: Fig.13 As shown in the long-term stability test, PVDF-GO-SiO 2 The composite nanofiltration membrane was continuously filtered for 70 hours, and the flux and retention rate of the nanofiltration membrane were recorded every 10 hours. The test results are as follows: Fig.14 shown.
[0199] from Fig.13 It can be seen that PVDF-GO-SiO 2 During the continuous filtration of the composite nanofiltration membrane for 24 hours, the water permeation flux and retention rate were relatively stable, and the dye flux was 13.30 L·m -2 ·h -1 The retention rate remains above 80%. 2 The composite nanofiltration membrane has good short-term stability when filtering inorganic salt solutions and has great application potential in the treatment of dye wastewater. Fig.14 PVDF-GO-SiO 2 The permeation flux of the composite nanofiltration membrane to the dye fluctuated slightly during the 70-hour continuous test and was basically maintained at 13.30 L·m -2 ·h -1 The dye retention rate is more than 80%, which shows that PVDF-GO-SiO 2 The composite nanofiltration membrane has good long-term stability.
Claims
1. A method for preparing a composite nanofiltration membrane modified by silica nanoparticles, characterized in that: The following steps are involved: S1, providing a mixed solution containing graphene oxide and silicon dioxide nanoparticles; S2, using a vacuum filtration method to form a graphene oxide functional layer on the base membrane with the mixed solution, and then performing a thermal cross-linking treatment to obtain a composite nanofiltration membrane modified by silica nanoparticles; Wherein, in step S1, in the mixed solution, the concentration of graphene oxide is 0.01wt% to 0.05wt%, and the concentration of silicon dioxide nanoparticles is 0.01wt% to 0.05wt%; In step S2, the amount of the mixed solution used is 0.50-1.50 mL / cm 2 .
2. The method for preparing a composite nanofiltration membrane modified by silica nanoparticles according to claim 1, characterized in that: In step S1, in the mixed solution, the concentration of graphene oxide is 0.04wt% to 0.05wt%, and the concentration of silicon dioxide nanoparticles is 0.03wt% to 0.05wt%; In step S2, the amount of the mixed solution used is 0.80-1.20 mL / cm 2 .
3. The method for preparing a composite nanofiltration membrane modified by silica nanoparticles according to any one of claims 1 to 2, characterized in that: In step S2, the conditions of the thermal cross-linking treatment include: a cross-linking temperature of 20 to 100°C and a cross-linking time of 4 to 12 hours.
4. The method for preparing a composite nanofiltration membrane modified by silica nanoparticles according to claim 3, characterized in that: In step S1, the particle size of the silicon dioxide nanoparticles is 45-55 nm.
5. The method for preparing a composite nanofiltration membrane modified by silica nanoparticles according to claim 4, characterized in that: In step S2, the negative pressure of the vacuum filtration is 0.8-1.0 MPa; and / or, During vacuum filtration, the ambient temperature must be maintained at 20-30°C and the humidity at 60%-70%.
6. The method for preparing a composite nanofiltration membrane modified by silica nanoparticles according to claim 5, characterized in that: In step S2, the base film is further subjected to a soaking treatment and a drying treatment in sequence before use; The soaking treatment comprises: soaking the base film in deionized water or toluene; The drying process includes: drying until there is no obvious moisture on the surface of the base film.
7. A composite nanofiltration membrane modified by silica nanoparticles prepared by the preparation method according to any one of claims 1 to 6, characterized in that: It comprises a base film and a graphene oxide functional layer, wherein the graphene oxide functional layer is loaded on the base film; The graphene oxide functional layer comprises graphene oxide nanosheets of layered structure and silicon dioxide nanoparticles intercalated and cross-linked in the graphene oxide nanosheets; The base film includes one or more of a polyvinylidene fluoride film, a polyethersulfone film, and a cellulose film.
8. The composite nanofiltration membrane modified by silica nanoparticles according to claim 7, characterized in that: The thickness of the graphene oxide functional layer is greater than 170 nm and less than 195 nm.
9. The composite nanofiltration membrane modified by silica nanoparticles according to claim 8, characterized in that: The Zeta potential of the composite nanofiltration membrane is enhanced in negative charge within the pH range of 3 to 9.
10. Use of a composite nanofiltration membrane modified based on silica nanoparticles prepared by the preparation method according to any one of claims 1 to 6 or a composite nanofiltration membrane modified based on silica nanoparticles according to any one of claims 7 to 9 in separating inorganic salts and dyes in water.
Citation Information
Patent Citations
Flexible high-flux graphene oxide / silicon dioxide composite film and preparation method thereof
CN110354696A
Method for preparing hydrophobic graphene film
CN111450711A
Cited By
Preparation method of nano silicon dioxide intercalation modified graphene composite material
CN120518067A
Preparation method and application of GO interlayer in-situ growth TiO2 composite membrane
CN122183402A